Relationship between serum bilirubin levels and optic neuritis - DENG, Juan; LIANG, Xue-mei; ZHANG, Xiu-lan; LING, Shi-qi; YANG, Ting-ting; LI, Min; PENG, Fu-hua (Chinese medical journal, 2013)
Background Bilirubin is the end product of heme catabolism and has strong antioxidant properties. Serum bilirubin levels are reported to be reduced in patients with multiple sclerosis （MS） and neuromyelitis optica （NMO）. The pathophysiology of optic neuritis （ON） resembles that of MS; however, the role of endogenous bilirubin in ON is unclear. The aim of this study is to measure serum bilirubin levels in patients with ON, and to investigate the correlation between ON and serum antioxidant status of bilirubin. Methods Serum levels of bilirubin were measured in 42 patients with ON, 50 patients with multiple sclerosis （MS）, 48 patients with neuromyelitis optica （NMO） and 48 healthy control subjects. Results Serum total bilirubin （Tbil）, direct bilirubin （Dbil） and indirect bilirubin （Ibil） levels in patients with ON were significantly lower than those in the healthy controls. However, no statistical significance was found between levels in the ON and MS, ON and NMO, and MS and NMO groups. In patients with ON, serum Tbil, Dbil, and Ibil levels were lower in those with recurrence or those with ON for a longer duration （〉1 year）. Moreover, Tbil, Dbil, and Ibil concentrations were lower in patients with papillitis than in those with retrobulbar type ON, but the differences were not statistically significant. Conclusions Low antioxidant status may exist in patients with ON. But serum levels of Tbil, Dbil, and Ibil did not correlate with clinical presentations, such as recurrence, duration of disease and subtypes of ON. Low antioxidant status already existed in MS or NMO patients before systemic symptoms appeared.